Efficacy and safety of transarterial infusion of anti-PD-1 in the treatment of advanced or metastatic acral and mucosal melanomas - Qianqi, Chen; Yan, Zhao; Yueqiang, Tang; Jiangman, Duan; Xiaohong, Fu; Qiming, Zhou (Cellular and Molecular Biology, 2022)
This study aimed to evaluate the efficacy and safety of transarterial infusion of programmed cell death receptor-1 (PD-1) antibody therapy in advanced or metastatic acral and mucosal melanomas. Eleven patients with acral or mucosal melanoma were referred to the department of Internal Medicine-Oncology in Huazhong University of Science and Technology Union Shenzhen Hospital from January 2019 to August 2020. These patients received transarterial infusions of PD-1 antibody and intravenous infusions of albumin-bound paclitaxel. The median duration of follow-up was 8 months. The patients were treated with transarterial infusion of PD-1 antibody and intravenous infusion of albumin-bound paclitaxel. in study, We collected and recorded immunotherapy-related adverse events. The results showed that the response rate (RR) and the disease control rate (DCR) of the patients (seven with acral melanoma, four with mucosal melanoma) were 54.5 % and 90.9 %, respectively. No grade 3–4 adverse events or major complications were observed during the study. The median progression-free survival was 10 months. The transarterial infusion of PD-1 antibody has remission and control effects on acral and mucosal melanomas, which is important for the clinical care of these patients.